FAKTOR PENENTU PILIHAN KONSUMEN KOMODITI PERTANIAN TERHADAP TEMPAT BERBELANJA DI PASAR TRADISIONAL DAN PASAR MODERN DI KOTA MANADO - Zely Ela Karouw; O. Esry H. Laoh; Juliana R. Mandei (Sam Ratulangi University, 2016)
This study aims to describe the factors which determine consumer decisions of agricultural commodities to shop at traditional markets and modern markets in the city of Manado. This study took place in June 2015 until July 2015 at Traditional and Modern Market Market in the city of Manado. In this study, the data used is primary data obtained from questionnaires and secondary data obtained from the relevant agencies, namely the Manado Statistics Central Agency (BPS) and Department of Industry and Trade of Manado. Variables measured were age, education level, income, location, product, price, atmosphere in the outlets, service, comfort, prestige. Analysis of the data used is the logistic regression model analysis.The results showed that there are two variables that significantly determine the consumer’s decision of choosing to shop in agricultural commodities at Traditional Market or Modern Market in the city of Manado is the atmosphere in the stores and services. Consumer’s who want a high atmospheric in the stores, preferring to go shopping to the modern market, while consumer’s who want good services, prefer to shop in tradisional market.